Examining coaches` perceptions of how their stress influences the coach-athlete relationship - Thelwell, R. C.; Wagstaff, C. R. D.; Chapman, M. T.; Kenttä, G (Journal of Sports Sciences, 2017)
This study extends recent coach stress research by evaluating how coaches perceive their stress experiences to affect athletes, and the broader coach-athlete relationship. A total of 12 coaches working across a range of team sports at the elite level took part in semi-structured interviews to investigate the 3 study aims: how they perceive athletes to detect signals of coach stress; how they perceive their stress experiences to affect athletes; and, how effective they perceive themselves to be when experiencing stress. Following content analysis, data suggested that coaches perceived athletes able to detect when they were experiencing stress typically via communication, behavioural, and stylistic cues. Although coaches perceived their stress to have some positive effects on athletes, the overwhelming effects were negative and affected "performance and development", "psychological and emotional", and "behavioural and interaction" factors. Coaches also perceived themselves to be less effective when stressed, and this was reflected in their perceptions of competence, self-awareness, and coaching quality. An impactful finding is that coaches are aware of how a range of stress responses are expressed by themselves, and to how they affect athletes, and their coaching quality. Altogether, findings support the emerging view that coach stress affects their own, and athlete performance.